Indikace k transplantaci jater a zařazování na čekací listinu - Husová, L (Vnitrni lekarstvi, 2013)
The authors have presented an overview of indications and inclusion of patients to the liver transplant waiting list in the Brno transplant centre over a period of 30 years from the first liver transplant performed in the Czech Republic (the then Czechoslovakia). The first clinical liver transplant in the Czech Republic was performed on 2 February 1983. Indication for the transplant was a malignant liver tumour. For a period of 30 years (from 2 February 1983 to 15 January 2013) a total of 592 patients were placed on the waiting list and a total of 453 liver transplants were performed. An urgent liver transplant was carried out in 32 patients over the same period of time.
Keywords: transplantace jater; Liver Neoplasms; seznamy čekatelů; nádory jater; Time Factors; Waiting Lists; Česká republika; mužské pohlaví; Patient Selection; Czech Republic; výběr pacientů; ženské pohlaví; Humans; Liver Transplantation; časové faktory; Carcinoma, Hepatocellular; Female; lidé; Male; hepatocelulární karcinom